Microsoft CEP Server and Online Behavioral Targeting - Ali, Mohamed; Gerea, Ciprian; Sezgin, Beysim; Tarnavski, Tiho; Verona, Tomer; Wang, Ping; Zabback, Peter; Kirilov, Anton; Ananthanarayan, Asvin; Lu, Ming; Raizman, Alex; Krishnan, Ramkumar; et al. (International Conference on Very Large Data Bases (VLDB), Lyon, France, 2009)
We present the Microsoft Complex Event Processing (CEP) Server, Microsoft CEP for short. Microsoft CEP is an event stream processing system featured by its declarative query language and its multiple consistency levels of stream query processing. Query composability, query fusing, and operator sharing are key features in the Microsoft CEP query processor. Moreover, the debugging and supportability tools of Microsoft CEP provide visibility of system internals to users. Web click analysis has been crucial to behavior-based online marketing. Streams of web click events provide a typical workload for a CEP server. Meanwhile, a CEP server with its processing capabilities plays a key role in web click analysis. This demo highlights the features of Microsoft CEP under a workload of web click events.